2005
DOI: 10.1099/vir.0.81259-0
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of human immunodeficiency virus type 2 coreceptor usage, autologous neutralization, envelope sequence and glycosylation

Abstract: To investigate why human immunodeficiency virus type 2 (HIV-2) is less virulent than HIV-1, the evolution of coreceptor usage, autologous neutralization, envelope sequence and glycosylation was studied in sequentially obtained virus isolates and sera from four HIV-2-infected individuals. Neutralization of primary HIV-2 isolates was tested by a cell line-based assay and IgG purified from patients' sera. Significant autologous neutralization was observed for the majority (39 of 54) of the HIV-2 serum–virus combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 63 publications
(101 reference statements)
4
80
0
Order By: Relevance
“…Clinical trials are therefore needed to determine if the MVC dosages recommended in HIV-1 infection are also effective for HIV-2 infection. This may prevent the administration of subtherapeutic dosages that favour the selection of X4 variants which, in HIV-2, have been associated not only with CD4 depletion and disease progression [2], but also with resistance to neutralization [16]. Similarly to previous results obtained with RANTES for HIV-2 [17] and with TAK-779 and C-C chemokines for HIV-1 [8,9], MVC inhibits the replication of R5 HIV-2 variants isolated from AIDS patients with significantly higher IC 50s than R5 variants isolated from asymptomatic patients, this being inversely associated with the number of CD4 + T-cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials are therefore needed to determine if the MVC dosages recommended in HIV-1 infection are also effective for HIV-2 infection. This may prevent the administration of subtherapeutic dosages that favour the selection of X4 variants which, in HIV-2, have been associated not only with CD4 depletion and disease progression [2], but also with resistance to neutralization [16]. Similarly to previous results obtained with RANTES for HIV-2 [17] and with TAK-779 and C-C chemokines for HIV-1 [8,9], MVC inhibits the replication of R5 HIV-2 variants isolated from AIDS patients with significantly higher IC 50s than R5 variants isolated from asymptomatic patients, this being inversely associated with the number of CD4 + T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to HIV-1, HIV-2 may enter cells without binding to CD4, and by using multiple alternative coreceptors besides CCR5 and CXCR4 [2,3]. This suggests that maraviroc (MVC), a CCR5 antagonist, might also have limited activity against HIV-2.…”
mentioning
confidence: 99%
“…P3P4, P7P8, and P9P10 are HIV-2 transmission chains (see Methods); the estimates therefore represent the mean evolutionary rate in two infected patients. The estimates for Shi et al [68] represent mean substitution rates in four individuals for which only limited sequences were available (see Methods). Found at doi:10.1371/journal.pcbi.0030029.st004 (60 KB DOC).…”
Section: Methodsmentioning
confidence: 99%
“…2; Table S1). In an interesting study, Shi and colleagues have observed in a four-PBMC-passage stock the conservation of L319R V3 , I320R V3 and K338E C3 mutations in viral isolates that efficiently use CXCR4 [54]. Probably, V3 and C3 interaction at these positions, which flank the amino acids F337 C3 and F321 V3 , which are already involved in the predicted non-covalent interaction [41].…”
Section: Discussionmentioning
confidence: 99%
“…In HIV-2, the net charge of the V3-loop is a determinant of co-receptor selection, like in HIV-1 [51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%